ANALISIS STRATEGI BAURAN PEMASARAN DAN PENGARUHNYA TERHADAP LOYALITAS KONSUMEN PADA ALFAMIDI KOTA GUNUNGSITOLI - RIFAIN ANUGRAH ZAI; YUPITER MENDROFA; SUMANGELI GULO (LP2MTBM MAKARIOZ, 2022)
The purpose of this study was to determine the Marketing Mix Strategy and how much influence the Marketing Mix has on Consumer Loyalty at Alfamidi, Gunungsitoli City. To achieve this goal, researchers process data using quantitative descriptive methods in the form of numbers or numbers. The type of data used is primary data with data collection techniques namely observation, interviews and technical questionnaires or questionnaires. Questionnaires were distributed to 40 respondents, namely Alfamidi Consumers, Gunungsitoli City.Based on the data collected from the research conducted, the results were obtained that: (1) Based on the results of the validity of the questionnaire items, it was obtained that the questionnaire prepared by the researcher met valid criteria or was suitable for use as a research data collection tool. (2) The influence of Marketing Mix Strategy on Alfamidi Consumer Loyalty in Gunungsitoli City is 44.80%. (3) Based on the results of hypothesis testing, namely the probability value of 0.000, the value is below 0.05 and the tcount value is 5.551, the value is above the research table, namely 2.042. it means that the marketing mix strategy (X) has a significant effect on consumer loyalty (Y), with a good marketing mix strategy able to increase consumer loyalty to Alfamidi, Gunungsitoli City. The test results prove that the marketing mix strategy has a positive and significant effect on consumer loyalty, and it can be said that Ho is rejected and Ha is accepted.